ANALISIS PERUBAHAN PENUTUPAN LAHAN DAN FAKTOR SOSIAL EKONOMI PENYEBAB DEFORESTASI DI CAGAR ALAM KAMOJANG - Vella Putikasari; Endes N Dahlan; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Land clearing as one of major activity in geothermal exploration and humans activity cause more deforestation in Kamojang Nature Reserve and disturb the role of forest as a storage of environmental services. The aim of this research is: 1) to measure the land cover change and determine the forest status of Kamojang nature reserve and 2) to identify socio-economic factors that cause deforestation. Analysis report from citra landsat showed us the type of land cover was dominated by forest for about 4231.26 ha with forest cover presentage around 51.17%. By that result, Kamojang nature reserve has been called as a disturbed status. In the other case, sosio-economic factors that cause deforestation were totally significant for salary and status of land tenure. Both of these factors significantly influence deforestation in the Kamojang Nature Reserve at 5% level of significance. The significance of one variable would have an effect to the forest deforestation. Those results of research reflected a part of effort in managing Kamojang Nature Reserve and geothermal environmental services. Keywords: Deforestation, Geothermal, Land cover, Socio-economic, Kamojang Nature Reserve